Tonal language in rhetoric _ green approach, red, yellow Onmozja_ - عبد السيد سلمان محمد (Journal of College of Education, 2018)
Color of the most important and most beautiful phenomena of nature, and the most important elements that make up the artistic and literary image. Color language is not the language of him, utter color inanimate objects and gives him the language, language in different civilizations were not the only way to express the truth, but it can be considered a color language is _ largely _alhakiqh that can not language be connected; what characterizes the ability of, and owned the implication and accuracy in the embodiment of meaning mechanisms , Vngdo read the language in the color space "pattern Tjdedea in the lexicon semantic, would meet art language, and meet the philosophy of expressing beauty philosophy of color, and elevate color language; they reflect the deep self" Moreover, the composition of chromatography and means of description is the psychological feeling in general, is important and the appearance of realism appearances in literary and artistic picture, and has also clarified a number of real and moral structures Remember, whether positive or negative, reflecting its what’s on in the innermost product of feelings and a sense of and orientations, so it was a squad of color with Icon aesthetic worthy of research and exploration; especially if it was excavated in the oasis of ancient of oases language Noon, namely rhetoric, who is rich from the definition and the statement approach; because the author identified himself and said: "and I princes speech and in us Tencpt his veins, and he Tahedlt Gsouna "from here sought search to be monitored in the study of color processors employed by the faithful (peace be upon him) in Nahj, to recognize the vulnerability of the faithful (peace be upon him) in color.